The Utilization of Augmented Reality as an Innovative Learning Media for PGMI Teacher Candidates: A Literature Review - Nurul Miftahul Ilmi; Putri Hasanah; Nouval Haikal Hazid; Desty Ayu Anastasha; Sunarti (AR-RIAYAH: Jurnal Pendidikan Dasar, 2026)
This research aims to comprehensively examine the use of Augmented Reality (AR) as an innovative learning medium for prospective teachers, especially in the context of Madrasah Ibtidaiyah Teacher Education. A literature review (LR) was conducted in 2021–2025, with literature searches through Google Scholar, ResearchGate, ScienceDirect, and DOAJ databases. Studies show that AR has great potential to increase students' desire to learn, student involvement, concept understanding, and pedagogical technology competencies of future teachers' knowledge content (TPACK). AR technology can transform abstract ideas into concrete, three-dimensional objects. This makes the learning experience more interactive and meaningful. The study found that incorporating AR into the PGMI curriculum is essential to improve the quality of education of prospective teachers, foster creativity, and increase readiness to face the challenges of 21st-century education. To optimize the use of AR, institutions must help through the provision of infrastructure, educational technology training, and supportive policies.